Modelos matemáticos, objetividad y libre elección - Báquiro Guerrero, Sebastián Alberto (2023)
Technical progress has allowed the development of increasingly powerful, fast and accurate tools, expressed in mathematical models. These are used for a more assertive and faster decision-making, lightening the individual burden of responsibility. However, these technical advances are more than just tools because what emerges from them is not simply neutral and impartial information pointing unequivocally towards the truth. In this way freedom, both individual and collective, is affected by the models and the context that encourages and sponsors these models from capitalism.